2010
DOI: 10.1002/14651858.cd000336.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of outpatient pharmacists' non-dispensing roles on patient outcomes and prescribing patterns

Abstract: BackgroundThe roles of pharmacists in patient care have expanded from the traditional tasks of dispensing medications and providing basic medication counseling to working with other health professionals and the public. Multiple reviews have evaluated the impact of pharmacist-provided patient care on health-related outcomes. Prior reviews have primarily focused on in-patient settings. This systematic review focuses on services provided by outpatient pharmacists in community or ambulatory care settings. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
230
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(244 citation statements)
references
References 169 publications
3
230
0
3
Order By: Relevance
“…Multiple studies have shown that medication reviews (which could include addressing confusion about medicine labels) by the pharmacist improve the clinical outcomes in patients. 38 Pharmaceutical care as a fairly new practice is still gaining acceptance as an integral part of health care. Lay expertise may influence this development as consumers continue to gain more knowledge through other nonprofessional sources.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…Multiple studies have shown that medication reviews (which could include addressing confusion about medicine labels) by the pharmacist improve the clinical outcomes in patients. 38 Pharmaceutical care as a fairly new practice is still gaining acceptance as an integral part of health care. Lay expertise may influence this development as consumers continue to gain more knowledge through other nonprofessional sources.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…This group of activities, articulated in the multi-professional and inter-sectorial actions, is also essential for ensuring access to quality medical drugs, and promotion of their appropriate use 8 . A systematic review 11 found that the majority of the studies included pointed to the importance of the action of pharmaceutical professionals in the management of therapy, in advising the patient and in training of health professionals in the improvement of the process of care and achievement of clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Services that a pharmacist could potentially offer to help consumers and their carers effectively manage chronic conditions include medication reviews, education and information, safety monitoring through reporting adverse drug reactions or interactions or both, supporting compliance through dose administration aids, and liaising with a person's General Practitioner (GP) and other health providers as part of a care plan. 11 Perhaps more contentiously, in selected countries, pharmacists can also prescribe in a range of models across varying scopes of practice.…”
Section: Introductionmentioning
confidence: 99%